INTRODUCTION SECTIONS IN CREATIVE ARTS THESIS - Su-Hie Ting; Saiful Bahari Mohamad Yusoff; Nancy Kissam (UIN Raden Mas Said Surakarta, 2022)
The content structuring of creative arts thesis is still evolving and has been mainly based on the social science thesis structure. However, the diversity of creative works encompassing music compositions, novels, art works, dance, and painting makes it difficult for the thesis to fit into the conventional content structure. There is also the description of intellectual property and the final product validation which are distinctly different components of creative arts research which need to be documented. In addition, the impetus for the creative arts research may not arise from a gap of knowledge in the field but from ergonomical problems of certain products or designs. The present study examined how the introduction section is written in creative arts thesis. Eleven creative arts theses written by undergraduate and postgraduate students in two Malaysian universities were analysed to identify the impetus or entry point for the research. The results indicate that the research problem in creative arts thesis is inclined towards researcher observation of ergonomic problems with existing products or designs although some students strengthen their case by citing related research findings on the weaknesses of existing products or design to carve a niche for their study. The study suggests that patent search offers useful information that can be used to justify the novelty of innovations and inventions.